Social inequalities in self-reported SARS-CoV-2 infection in Brazilian adults: PNAD COVID-19 - Mateus Andrade Rocha; Cândido Norberto Bronzoni de Mattos; Marcos Pascoal Pattussi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To investigate inequalities related to race/ethnicity and socioeconomic status in self-reported positive diagnosis for COVID-19 in Brazilian adults. Methods: Data available from the National Household Sample Survey COVID-19 (PNAD COVID 19) (July/September/November, 2020) were used in this retrospective investigation. The analyses considered the sampling design, primary sampling units, strata and sample weights. Poisson regression with robust variance was used to estimate prevalence ratio (PR) and the 95% confidence interval (95%CI) of the associations. Results: In July, September and November 2020, with regard to the rapid test, indigenous people were 2.45 (95%CI 1.48-4.08), 2.53 (95%CI 1.74-4.41) and 1.23 (95%CI 1.11-1.86) times more likely to report a positive history of SARS-CoV-2 infection, respectively. With regard to the RT-PCR test in November, indigenous people were more likely to test positive for COVID-19 (PR: 1.90; 95%CI 1.07-3.38). It was observed that the indigenous group was 1.86 (95%CI 1.05-3.29) and 2.11 (95%CI 1.12-3.59) times more likely to test positive for COVID-19 in September and November (2020). Income was associated with testing positive for COVID-19: in November, individuals whose income ranged from R$0.00-R$1.044 were more likely (PR: 1.69; 95%CI 1.16-23.06) to test positive using the RT-PCR test; participants whose income was in this range were also more likely to be diagnosed with COVID-19 using blood tests (PR: 1.72; 95%CI 1.43-2.07). Conclusion: The data presented show an association between race/ethnicity and economic status with a positive diagnosis of COVID-19.